How to bargain successfully with adolescents: What can be learned from youth development professionals. Issue 7 (6th March 2021) - Perry, S. Cole; Izenstark, Dina; Larson, Reed
Abstract: This study examines risks and potential benefits that youth professionals experience in bargaining with adolescents. We conducted semistructured qualitative interviews with 50 experienced adult leaders of 27 high‐quality arts, technology, and leadership youth programs (serving ethnically‐diverse teens). Half worked with younger teens (ages 11–14), half with older (ages 14–18). Leaders reported bargaining in ways responsive to youth's wants and needs, reaching win‐win agreements. Leaders of younger youth experienced more risks in bargaining, so took greater control over what was bargained. They used bargains most often to motivate when youth's enthusiasm dropped, and these bargains sometimes helped youth develop self‐motivation. Leaders of older youth reported fewer risks and more benefits. They bargained as equals, asking youth to share decision‐making responsibility. They used bargaining as a pedagogical tool to model, support, and challenge youth, which helped build their capacities for deliberative decision‐making. The findings illuminate strategies for practitioners to use bargaining effectively.